Problematika Menyusun RPP Mahasiswa PGSD Pada Era New Normal - Putri Utami, Ima Wahyu (Universitas PGRI Adi Buana Surabaya, 2021)
Learning that is done now and a few years ago underwent a transformation of the education system. Learning that is done now does not allow us to carry out face-to-face learning activities, all aspects of education are carried out online. This also has an impact on the courses that teach preparing lesson plans. This study aims to describe the problems of students in preparing lesson plans. The results of this study indicate that the problems faced by students in preparing lesson plans are both content and technical. In the preparation of a complex lesson plan, students experience problems in certain parts. While the learning tools made must be interrelated. So if students experience problems in certain parts of the learning device, then this will have an impact on the preparation of other parts of the learning device.